2021
DOI: 10.3390/foods10102268
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Ginger Essential Oil Microcapsule Composite Films

Abstract: New food packaging has shown research significance in the face of increasing demand for high-quality foods and growing attention paid to food safety. In this study, ginger essential oil microcapsule composite films were prepared by combining microcapsules prepared by a complex coacervation method with gelatin films, and the mechanical properties and active functions of the composite films were analyzed. Fourier-transform infrared spectroscopy and differential scanning calorimetry confirmed the successful encap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…Compared with 10 min, the reducing power of β-CD-IvEO-ICs increased substantially in 1 h reaction time, which could be due to the controlled release of IvEO in inclusion complexes, resulting in stronger antioxidative activities as the reaction time was extended. This phenomenon was in line with those observed in studies (Khatibi et al, 2021;Wang et al, 2021).…”
Section: Ta B L Esupporting
confidence: 93%
“…Compared with 10 min, the reducing power of β-CD-IvEO-ICs increased substantially in 1 h reaction time, which could be due to the controlled release of IvEO in inclusion complexes, resulting in stronger antioxidative activities as the reaction time was extended. This phenomenon was in line with those observed in studies (Khatibi et al, 2021;Wang et al, 2021).…”
Section: Ta B L Esupporting
confidence: 93%
“…Conversely, PEO in the PEOM must be penetrated the wall of GE, and gradual release under the same conditions. The results of comparison showed that the antioxidant activity of PEOM was found to be more sustainable than PEO, results consistent with those of Wang et al ( 32 ).…”
Section: Resultssupporting
confidence: 89%
“…Sample pretreatment of PEOM was carried out as described by Wang et al ( 32 ). Briefly, antioxidant capacity and antibacterial activity were measured every 1 day, during 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…The compositions, structures, and functional groups of essential oils play a role in determining their antibacterial activity [11] . However, it is known that the effectiveness of the GEO as an antibacterial activity is poor due to its instability in the environment, high volatility, and susceptibility to temperature, humidity, or oxidation, thus limiting its application [12] …”
Section: Introductionmentioning
confidence: 99%
“…[11] However, it is known that the effectiveness of the GEO as an antibacterial activity is poor due to its instability in the environment, high volatility, and susceptibility to temperature, humidity, or oxidation, thus limiting its application. [12] [a…”
mentioning
confidence: 99%